2020
DOI: 10.1515/revneuro-2019-0112
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic and glutamatergic effects on nigrostriatal and mesolimbic dopamine release in the rat

Abstract: AbstractIn this review, a series of experiments is presented, in which γ-amino butyric acid (GABA)ergic and glutamatergic effects on dopamine function in the rat nigrostriatal and mesolimbic system was systematically assessed after pharmacological challenge with GABAA receptor (R) and and N-methyl d-aspartate (NMDA)R agonists and antagonists. In these studies, [123I]iodobenzamide binding to the D2/3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…Nikolaus and colleagues presented a series of experiments exploring the effects of agonists and antagonists at both GABA A receptors and NMDARs on dopamine controls in mesolimbic and mesostriatal pathways. They observed that the GABA A receptor agonist muscimol and the NMDAR antagonist amantadine exert similar actions on regional dopamine release, supporting the hypothesis of triple glutamate—GABA—dopamine interaction underlying the dysfunctions observed in schizophrenia [ 89 , 90 ].…”
Section: Dopamine–glutamate Interaction and The Role Of D-amino Acidsmentioning
confidence: 85%
“…Nikolaus and colleagues presented a series of experiments exploring the effects of agonists and antagonists at both GABA A receptors and NMDARs on dopamine controls in mesolimbic and mesostriatal pathways. They observed that the GABA A receptor agonist muscimol and the NMDAR antagonist amantadine exert similar actions on regional dopamine release, supporting the hypothesis of triple glutamate—GABA—dopamine interaction underlying the dysfunctions observed in schizophrenia [ 89 , 90 ].…”
Section: Dopamine–glutamate Interaction and The Role Of D-amino Acidsmentioning
confidence: 85%
“…We summarize this D2-dependent inhibitory effect on V 0 to be a rate constant k V times the current D2 AR value. In addition to the D2-dependent inhibitory regulation through negative feedback, midbrain DAergic neurons also exhibit D2-independent excitatory coupling through positive PLOS COMPUTATIONAL BIOLOGY feedback [98][99][100]. These excitatory effects are defined as proportional to the current firing rate F times a rate constant b that reflects the conversion strength from neuron activity to neuron electrochemical state.…”
mentioning
confidence: 99%